2022
DOI: 10.1088/1755-1315/1115/1/012076
|View full text |Cite
|
Sign up to set email alerts
|

The role of various plastisizers and fillers additions in improving tensile strength of starch-based bioplastics: A mini review

Abstract: The general public uses plastic extensively, particularly in food packaging. Plastic raw materials are generally petroleum derivatives with advantages such as high tensile strength, low cost, lightweight, ease of manufacture, and application. However, there are other disadvantages to plastic, which is not easily biodegradable. As a result, researchers have expressed a strong desire to develop biodegradable plastics in order to reduce the accumulation of non-biodegradable plastics in the environment. One of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…In general, the starch-based bioplastics show lesser strength [29] and it was reported that the strength of corn starch bioplastics was 2.57 MPa [30] and a relatively a higher strength of 8.43 MPa was achieved with 20 % CMC addition, [29] 13.42 MPa in the case of 30 % sorbitol addition. [31] Tan et al reported an optimum strength of 5.19 MPa and an elongation of 44.6 % in corn starch bioplastic.…”
Section: Discussionmentioning
confidence: 96%
“…In general, the starch-based bioplastics show lesser strength [29] and it was reported that the strength of corn starch bioplastics was 2.57 MPa [30] and a relatively a higher strength of 8.43 MPa was achieved with 20 % CMC addition, [29] 13.42 MPa in the case of 30 % sorbitol addition. [31] Tan et al reported an optimum strength of 5.19 MPa and an elongation of 44.6 % in corn starch bioplastic.…”
Section: Discussionmentioning
confidence: 96%
“…Apart from that, the more PLA the composition, the better the biodegradation process will occur, this shows that PLA has good degradability. Meanwhile, using more PCL composition than PLA will give an irregular degradation percentage along with the addition of chitosan [12]. PLA and PCL are biopolymers that have the ability to degrade biologically in the soil because they are obtained from renewable sources.…”
Section: Biodegradation Analysismentioning
confidence: 99%
“…The active packaging production process based on PLA is easier because it employs commercial tools. However, PLA has a drawback for active packaging applications due to its low water vapor barrier properties, rigidity, and heat distortion temperatures ([ 5 , 6 ]). Combining PLA with other biocompatible aliphatic polyesters, such as poly ε-caprolactone (PCL), is expected to compensate for these drawbacks.…”
Section: Introductionmentioning
confidence: 99%